Socio-economic analysis and profitability of small-scale broiler production enterprises in Vhembe District, Limpopo Province - Mulaudzi, Rudzani Grace (My University, 2015)
The aim of the study was to analyse the socio-economic factors affecting the gross margin of small-scale broiler producers in the Vhembe district and thereby determine their profitability and contribution towards the local economic development. The population comprised of small-scale broiler producers who reared between100 and 3200 birds in the Vhembe district. A total of 94 out of 311small-scale broiler producers were selected using a simple random- sampling procedure. Data on different socio-economic parameters was collected through personal interviews using a semi-structured questionnaire. Descriptive statistics was computed using FREQ COUNTS procedures to describe the characteristics of small-scale broiler producers. Gross margin analysis was used to calculate the profitability for small-scale broiler producers. The Multiple Linear Regression was used to estimate the influence of socio-economic factors influence on the gross margin of the small-scale broiler producers. Multiple Regression analysis indicated that small-scale broiler producers in the Vhembe district were making profit. Socio-economic variables such as age of the farmer, farming experience, flock size, training received by the farmer, market access and record keeping, educational level, household income and extension services were found to have positive correlation with the small-scale broiler producers‟ gross margin. To effectively address production constraints affecting gross margin of small-scale broiler producers, it is, therefore, fundamental to consider their socio-economic profiles.
Thesis (M.A. (Agricultural Extension)) -- University of Limpopo, 2015
Keywords: Broiler producers; Chickens; Broiler production; Broilers (Poultry); Chicken breeders; Poultry -- Breeding; Chickens